Solubility and dissolution rate improvement of the inclusion complex of apigenin with 2-hydroxypropyl-β-cyclodextrin prepared using the liquid antisolvent precipitation and solvent removal combination methods. (3rd August 2017) - Wu, Weiwei; Zu, Yuangang; Zhao, Xiuhua; Zhang, Xinxin; Wang, Lingling; Li, Yuanyuan; Wang, Li; Zhang, Yin; Lian, Bolin
Abstract: Apigenin (AP) has many pharmacological activities. AP has poor solubility in some solvents. AP is insoluble in water and slightly soluble in ethanol (1.93 mg/ml). It has limited application and exploitation. Therefore, the liquid antisolvent precipitation (LAP) method was applied to improve the solubility of AP in ethanol by changing its crystal form or producing ultra-fine particles. Then, the inclusion complex of AP with 2-Hydroxypropyl-β-cyclodextrin (HP-β-CD) is prepared using the solvent removal method. The effects of various experimental parameters on the solubility of AP in ethanol were investigated through the single factor design. Under the optimum conditions, the AP–ethanol solution of 6.19 mg/ml was obtained. The inclusion complex of AP with HP-β-CD was obtained by the solvent removal method. The load efficiency (LE) and drug encapsulation efficiency (EE) of the inclusion complex of AP with HP-β-CD were 13.98%±0.14% and 97.86%±1.07%, respectively. SEM, FTIR, 1 HNMR, XRD, DSC and TG were used to analyze the characteristics of the inclusion complex of AP with HP-β-CD. These results showed that the inclusion complex has significantly different characteristics with AP. In addition, the dissolution rate and solubility of the inclusion complex were approximately 15.24 and 68.7 times higher than AP in artificial gastric juice, and was separately 10.4 times and 40.05 times higher than AP in artificial intestinal juice. The bioavailability of inclusion complex increased 3.97 times compared with AP.